Perspectivas sobre a eficiência da formação continuada de professores de escolas multisseriadas rurais - Roratto, Rodrigo (2023)
This thesis research, linked to Research Line: LP 1 - Training, Knowledge, and Professional Development of the Postgraduate Program in Education, emerges from the need for a study that can glimpse whether the actions and/or public policies aimed at continuing education for teachers are appropriate in the context of rural multigrade schools, given the lack of studies on the subject in the literature and the importance for society to know if actions promoted by the government generate, or not, waste of resources intended for the segment of basic education, and contribute to subsidies for governmental decision-making in this spectrum. Therefore, this research aims to analyze and understand whether or not the continuing education of teachers is efficient in rural multigrade schools belonging to the municipal and state education networks, located in the central region of Rio Grande do Sul, in the sense of adequacy to the context lived by the teachers. The choice of the central region for the study was made due to the amplitude of its area of coverage, which, added to the closing of several rural schools in this region over the last few years, can contribute to the understanding of several phenomena related to the theme and thus allow a scientific advance in the field of Education. To carry out the research, a qualitative and quantitative approach was adopted, of descriptive and exploratory nature in the form of a case study, with field research based on the perception of the evaluated school principals, through data analysis by technical and political perspectives. The results found in the technical perspective point to partial efficiency in most of the dimensions analyzed, especially the Innovations dimension, which reached full efficiency in all the school networks surveyed. As for the political perspective, the results indicate that all public school systems studied reached a level of partial efficiency, where no school system was inefficient regarding the policy of permanent training for teachers in rural multigrade schools. However, both the technical and political perspectives indicate the need for advances in some key points related to continuing education for teachers, both in the macro-action spectrum, in the dimensions of efficiency, and in the micro-action, in the public networks researched.